2020
DOI: 10.1093/pubmed/fdaa228
|View full text |Cite
|
Sign up to set email alerts
|

Poverty and survival from COVID-19 in Mexico

Abstract: Background Recent evidence points to the relevance of poverty and inequality as factors affecting the spread and mortality of the COVID-19 pandemic in Latin America. This study aimed to determine whether COVID-19 patients living in Mexican municipalities with high levels of poverty have a lower survival compared with those living in municipalities with low levels. Methods Retrospective cohort study. Secondary data was used to define the exposure (multidimensional povert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
2
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 26 publications
3
21
2
5
Order By: Relevance
“…Data from the United States (USA) has shown that low socioeconomic status, and race as its proxy, were significantly associated with COVID-19 incidence and mortality 7 . Similar findings have been reported in the United Kingdom (UK) [8][9][10] . Data from Brazil and Mexico further support the idea that the poorest population groups have lower survival from COVID-19 9,10 .…”
Section: Introductionsupporting
confidence: 91%
See 1 more Smart Citation
“…Data from the United States (USA) has shown that low socioeconomic status, and race as its proxy, were significantly associated with COVID-19 incidence and mortality 7 . Similar findings have been reported in the United Kingdom (UK) [8][9][10] . Data from Brazil and Mexico further support the idea that the poorest population groups have lower survival from COVID-19 9,10 .…”
Section: Introductionsupporting
confidence: 91%
“…Similar findings have been reported in the United Kingdom (UK) [8][9][10] . Data from Brazil and Mexico further support the idea that the poorest population groups have lower survival from COVID-19 9,10 .…”
Section: Introductionsupporting
confidence: 91%
“…Unlike previous studies that analysed the effect of income at the patient level, 18 , 19 our dataset includes information on pre-existing health conditions, and thus allows us to test whether comorbidities are a likely mechanism behind the association between income and COVID-19 mortality. In contrast to the existing literature on the association of socioeconomic vulnerability and COVID-19 severity in Mexico, 22 , 23 , 24 , 26 we are able to link COVID-19 outcomes to individual-level earnings data. Finally, lack of healthcare access is not a relevant variable here since all the individuals in our study had such access through the numerous facilities of IMSS (clinics and hospitals around the country).…”
Section: Introductioncontrasting
confidence: 69%
“…Gutiérrez and Bertozzi 22 and Millán-Guerrero et al. 23 found that higher poverty is positively associated with hospitalisation and death. Ortiz-Hernández and Pérez-Sastré 24 and Bello-Chavolla et al.…”
Section: Introductionmentioning
confidence: 98%
“…Absent travel restrictions between cities and states, or international travel, the patchwork of policy responses allowed the virus – and in Brazil deadly variants such as the Gamma variant – to spread and seed itself around the world. The outcomes have been especially severe in dense, low-income, urban communities, where poverty and informality drive people to work [ 2 , 78 ].…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%